Transformasi Bisnis Komoditas Cabai di NTB: Analisis Disparitas Pertumbuhan Cabai Merah dan Cabai Rawit 2013–2022 - Leni Yupita Rizki; Nabila Silvana; Tiara Nabila Huda; Karina Juniarti Utami; Herie Saksono (Penerbit Indocamp, 2024)
Chili is a strategic horticultural commodity with high economic value in the Indonesian economy. This longitudinal study analyzes the dynamics of chili business growth in West Nusa Tenggara Province during the 2013-2022 period, focusing on growth disparities between red chili and cayenne pepper. Although many studies have examined chili farming from various aspects, there is a literature gap in analyzing comparative long-term growth performance between the two chili varieties, particularly in NTB. The main problem is the unclear growth patterns differentiating the two commodities, which hinders the development of appropriate business strategies. This research aims to analyze the growth dynamics of both commodities and formulate strategic implications for sustainable chili agribusiness development. Using a quantitative approach with a longitudinal design based on time series data from